Racial Inequality, Ethnic Inequality, and the System Involvement of At-Risk Youth: Implications for the Racial Invariance and Latino Paradox Theses. (28th July 2016) - Wright, Kevin A.; Turanovic, Jillian J.; Rodriguez, Nancy
Abstract : Drawing from the inequality and crime, racial invariance, and Latino paradox literatures, the effects of inequality on youth reoffending are examined. Specifically, hierarchical logistic regression models are estimated to determine: (1) whether racial and ethnic inequality have similar contextual effects on the continued delinquent behavior of at-risk youth and (2) whether these effects are specific to black or Latino/a youth residing in Maricopa County, Arizona ( N  = 13, 138). Findings suggest that racial inequality increases reoffending while ethnic inequality decreases reoffending. Additionally, Latino/a youth are less likely to reoffend in areas characterized by high income and racial inequality. Structural theories of crime should continue to account for the importance of culture and the resilient responses employed by Latinos/as living in criminogenic environments.